2000
DOI: 10.1094/mpmi.2000.13.4.384
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing in the Plant Pathogen Erwinia carotovora subsp. carotovora: The Role of expREcc

Abstract: The production of the main virulence determinants of the plant pathogen Erwinia carotovora subsp. carotovora, the extracellular cell wall-degrading enzymes, is partly controlled by the diffusible signal molecule N-(3-oxohexanoyl)-L-homoserine lactone (OHHL). OHHL is synthesized by the product of the expI/carI gene. Linked to expI we found a gene encoding a putative transcriptional regulator of the LuxR-family. This gene, expR(Ecc), is transcribed convergently to the expI gene and the two open reading frames ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 57 publications
2
81
0
1
Order By: Relevance
“…The absence of a signal with SCRI193 chromosomal DNA in our assay could have been due to a low level of homology between expR2 of Ecc71 and the corresponding gene in SCRI193. We note that expR1 has been identified previously (1,7) in some of the strains used by Burr et al After taking into consideration all of these observations, we concluded that the QS system of E. carotovora subspecies consists of ExpR1, ExpR2, and AhlI, the AHL synthase. As shown in Fig.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The absence of a signal with SCRI193 chromosomal DNA in our assay could have been due to a low level of homology between expR2 of Ecc71 and the corresponding gene in SCRI193. We note that expR1 has been identified previously (1,7) in some of the strains used by Burr et al After taking into consideration all of these observations, we concluded that the QS system of E. carotovora subspecies consists of ExpR1, ExpR2, and AhlI, the AHL synthase. As shown in Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies demonstrated that mutation of ExpR1 in an AhlI ϩ background had no effect on the levels of RsmA and exoenzymes (1,12). We attribute the lack of effects of ExpR1 or ExpR2 in the AhlI ϩ strain to neutralization of ExpR variants by activities of AHL analogs.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Once bound, LuxR facilitates the binding of RNA polymerase to the target promoter (157)(158)(159), leading to activation of transcription. Although most instances show AHLbound LuxR-type proteins to function as transcriptional activators, a few examples of these proteins have been reported to function as repressors (2,13,15).…”
Section: Quorum-sensing Regulatorsmentioning
confidence: 99%